ANALISIS KEBERHASILAN PENGAJARAN PRAKTIK TERBAIK DALAM MATA KULIAH PSIKOLOGI PENDIDIKAN TINGKAT UNIVERSITAS - Wulandari, Deniar; Setiawan, Rudy; Arifendi, Rio Febrianto (Inteligensi : Jurnal Ilmu Pendidikan, 2023)
The purpose of this study was to analyze the success of practitioner teaching in learning Educational Psychology courses at Tribhuwana Tunggadewi University. This study used a best practice review approach to identify effective teaching strategies used by practitioners in that context. The research methods used involve classroom observation, interviews with practitioners, and qualitative analysis of documents. Practitioners use an active and collaborative learning approach, engage students in discussions and case studies, and encourage self-reflection with the help of relevant audiovisual media and reading materials. It was found that practitioners' success in teaching Educational Psychology is related to competence in integrating theory with relevant practical examples, relating material to students' real lives, and providing constructive feedback. In addition, practitioners also build inclusive learning environments, support students' active participation, and create an atmosphere that facilitates deep understanding. The results show that teaching with practice has been successfully carried out in teaching Educational Psychology courses, with implications related to the development of teaching competencies and the application of best practices in teaching Educational Psychology courses.